Leaf mineral composition of grafted eggplant grown in soil infested with Verticillium and root-knot nematodes - Çürük, Sebahattin; Dasgan, H. Yildiz; Mansuroğlu, Sedat; Kurt, Şener; Mazmanoğlu, Meltem; Tarla, Gülcan; Durgaç, Coşkun (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to determine differences in leaf mineral composition between ungrafted and grafted onto (Solanum torvum) eggplant (Solanum melongena), cultivars 'Faselis' and 'Pala', grown in a soil infested with Verticillium dahliae and Meloidogyne incognita, or in a noninfested soil. Grafting increased leaf P and Mn concentrations, and decreased N concentrations, in both soils. Grafting also enhanced leaf Ca concentration of 'Pala', but it did not affect that of 'Faselis' depending on the cropping year. Leaf Mg concentration of grafted plants in infested soil was lower than that of ungrafted ones in noninfested soil. Results showed that, under the same fertilization program, the grafted 'Faselis' plants used the nutrients more efficiently than the 'Pala' ones. Use of S. torvum as a rootstock for 'Faselis' resulted in an effective protection against multiple pathogen infestation. Fertilization may be necessary when grafted 'Faselis' plants are grown in a soil infested with the pathogens, since grafting and infestation generally decrease leaf N, Mg, Ca and Fe concentrations, either by reducing the nutrient concentrations directly or by increasing leaf Mn concentration.
Keywords: Meloidogyne incognita; Solanum melongena; Solanum torvum; mineral nutrition; multiple pathogen infestation